KESANTUNAN BERBAHASA GURU TERHADAP SISWA DAN IMPLIKASINYA DALAM PEMBELAJARAN DI MADRASAH TSANAWIYAH ALKHAIRAAT BALIASE - Rosnita; Hadija Alaydrus, Siti; Laki, Ridwan; Idrus; Afandi, Al (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines teachers' language politeness toward students and its implications for classroom learning interactions at MTs Alkhairaat Baliase. The study was motivated by the observation that teachers' ways of speaking influence classroom atmosphere, student participation, and the quality of teacher–student interaction, particularly among junior secondary school students who are highly sensitive to verbal treatment. The objectives of this study were to describe the forms of teachers' language politeness and to explain their role in shaping learning atmosphere and classroom interaction. This research employed a descriptive qualitative approach. The data consisted of teachers' utterances, students' responses, classroom interactions, interview results, and field notes collected through observation, recording, and interviews. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed 25 politeness-related data. Based on Brown and Levinson's theory, 16 data reflected positive politeness strategies and 9 data reflected bald-on-record strategies. Based on Leech's politeness principles, the data consisted of 10 agreement maxims, 4 tact maxims, 2 approbation maxims, and 8 violations of the approbation maxim. The findings indicate that polite language use by teachers contributes positively to creating a comfortable learning environment, encouraging student participation, increasing confidence in responding to questions, and fostering two-way interaction. Conversely, violations of politeness tended to reduce student participation by generating feelings of fear, embarrassment, and reluctance to engage in classroom interaction.